A test for DDT-resistant flies - Busvine, J.R. (University of Ceylon. Colombo, 1949)
In many districts of ceylon, house spraying with DDT has been done regularly for about two years as an anti-malarial measure. Some tests are described which were undertaken to determine whether flies (musca vicina) from a sprayed village had increased in resistance to DDT. To this end, they were reared in the laboratory, side by side with flies derived from an unsprayed area. No significant difference in average DDT knockdown time was found in these two strains. On the other hand the test showed a definite difference in resistance between two Italian strains, reared for twenty generations in London.
Keywords: Biological Sciences; Insecticides; Drug resistance; Pharmacology; Tropical medicine; Musca vicina